Physico-chemical study of the systems on the basis of sodium and ammonium perchlorate; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Trunin А. S.; Makarov А. F.; Yulina I. V.; Zipayev D. V. (Chemistry, 2007)
Заглавие с титульного листа